1994
DOI: 10.2355/isijinternational.34.346
|View full text |Cite
|
Sign up to set email alerts
|

SANS Study of Phase Decomposition in Fe-Cu Alloy with Ni and Mn Addition.

Abstract: Small-angle neutron scattering (SANS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 0 publications
3
33
0
Order By: Relevance
“…The results of this study predict that bcc Cu precipitates with Cu-rich concentrations, in a binary Fe-Cu alloy, are mechanically unstable, which is consistent with APT observations showing significant quantities of Fe in Cu precipitates with about 2-nm radius. [20,27,28,30,58,59] Nickel and Mn spherical shell enrichment has been observed for model Fe-Cu-Ni and Fe-Cu-Ni-Mn steels, [30,58,59,[62][63][64] but the concomitant enrichment in Al is a new result. Approximately equal proportions of Ni and Al in the spherical shell surrounding the Cu-rich core at 100 hours of aging may possibly be related to formation of a B2 ordered intermetallic phase.…”
Section: Atom-probe Tomographymentioning
confidence: 82%
“…The results of this study predict that bcc Cu precipitates with Cu-rich concentrations, in a binary Fe-Cu alloy, are mechanically unstable, which is consistent with APT observations showing significant quantities of Fe in Cu precipitates with about 2-nm radius. [20,27,28,30,58,59] Nickel and Mn spherical shell enrichment has been observed for model Fe-Cu-Ni and Fe-Cu-Ni-Mn steels, [30,58,59,[62][63][64] but the concomitant enrichment in Al is a new result. Approximately equal proportions of Ni and Al in the spherical shell surrounding the Cu-rich core at 100 hours of aging may possibly be related to formation of a B2 ordered intermetallic phase.…”
Section: Atom-probe Tomographymentioning
confidence: 82%
“…[1][2][3][4][5][6][7][8][9] In the previous study, 10) the spinodal decomposition of the (bcc) phase in an Fe-Cu-MnNi quaternary alloy, which is a base system of the light-water reactor pressure vessel, 11,12) was simulated by using the phase-field method, and it was pointed out that the segregation of Mn and Ni takes place at the surface of (bcc) Cu particles. However, the experimental investigation by Osamura et al 13) concluded that this segregation is not observed at the surface of the Cu particles but instead at the surface of (fcc) Cu particles. Isheim et al 14) have also recently confirmed the segregation of Mn and Ni at the surface of the Cu particles.…”
Section: Introductionmentioning
confidence: 90%
“…Using the features of SAS, the application to Fe-Cu alloys has been reported by Osamura et al using SANS 5,6) and Deschamps et al by SAXS. 7) Deschamps et al also reported detailed analysis of the microstructure evolution of Al alloys by time-resolved SAXS.…”
Section: Intermediate-angle Neutron Scattering Instrument For Quantitmentioning
confidence: 99%